"Pode a subalterna falar?": uma leitura crítica da crítica de Gayatri Spivak - Baltazar, Isabella Cristina Milagres (2019)
We propose a critical reading of some theoretical propositions of the literary critic Gayatri Chacravorty Spivak, icon of Indian Subaltern Studies, still insufficiently translated into the Portuguese language, that problematizes the "intellectual" that speaks "on behalf of" the silenced voice, at the same time in which she thematizes the "translation" of the subaltern message in its [im]possibilities of agency. In the book that inspires title to the thesis proposed here, Spivak focuses on the concept of subalternity to explore models of representation. Inspired by some of her inquiries in the fields of subaltern studies, literary criticism, and postcolonial feminism, we propose a problematization of her theoretical articulations marked by the transdisciplinary aspects of her production, in order to elucidate the reason for her worldwide academic influence. The problematic axis of this thesis starts from a theoretical interlocution between Jacques Rancière [2009] and Jacques Derrida [1973], with the aim of proposing a critique of the critique, understood as a power of democracy, a regime with no origin and no destination; and with the second one, to observe how the author actualizes the critique of Western metaphysics by incorporating in it the American system of domination, in order to finally make a critique of Spivak's theory: the verification of the existence of a metaphysical-theoretical agency of the US colonial system - which is why the philosophers Gilles Deleuze and Félix Guattari have also been incorporated, especially in view of the concept of agency developed by them both in the book A Thousand Plateaus: Capitalism and Schizophrenia [1980]. Taking as its basis authors who are constantly questioned by Spivak, the thesis also tries to observe how the arguments put forward by the Indian theoretician lack epistemological rigor either because they focus on the critique of the European colonial system, totally disregarding the subjective technologies of Yankee domination; or because part of the latter without considering much of the so-called Third World, although it has succeeded in decolonizing itself from Eurocentric domination seems, in our view, is basically sandwiched and impeded by the American metaphysical system.